A New School With Spaces Inclusive Pedagogics - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2021)
The current public policies in education matters of the Chilean State have declared within their focus the educational inclusion and a new public quality education that offers the best opportunities to all its inhabitants, especially to the most vulnerable socially, culturally and economically. In this way, it takes the international commitment mandated by the United Nations in the 2030 Agenda for Sustainable Development, in particular the Sustainable Development Goal 4, whose objective is to guarantee an inclusive and equitable quality education and to promote opportunities of permanent learning for all. The objective of this investigation considers studying the attitudes of pedagogy students to promote the inclusive school’s development. It is necessary, therefore, to know what they think and feel one of their main actors that will lead these changes, future teachers. This study was developed under a quantitative, multivariate, descriptive and correlational model of the phenomenon based on the general perceptions of the sample according to the studied construct. The data collection was carried out through the adaptation to the Chilean reality of the "Questionnaire for future Secondary Education teachers about perceptions of attention to diversity" (Colmenero & Pegalajar , 2015). The results show a positive perception towards inclusion of students, but it is necessary materialized them in a better initial teacher training and in real inclusion practices.